A new species of mecochirid lobster, Meyeria libanotica (Decapoda, Glypheoidea), from the Barremian (Early Cretaceous) of Lebanon - Charbonnier, Sylvain; Audo, Denis; Garassino, Alessandro; Simpsone, Martin; Geze, Raymond; Azar, Dany (Annales de Paléontologie, 2021)
A large sample of mecochirid lobsters (Crustacea, Decapoda, Mecochiridae) has been recently collected from the early Barremian (Early Cretaceous) of Lebanon. The studied specimens are described as Meyeria libanotica sp. nov. The genus Meyeria M'Coy, 1849 is also revised and new combinations are proposed for two species: Meyeria bartholomaii (Jell, Woods, and Cook, 2017) comb. nov. (Aptian, Australia), and Meyeria rostrata (Collins and Rasmussen, 1992) comb. nov. (Campanian-Maastrichtian, Greenland). The stratigraphic range and the palaeogeographic distribution of Meyeria are consequently recognized to spread from the Oxfordian (Late Jurassic) to the Maastrichtian (Late Cretaceous) and from Australia to Greenland, passing by Europe, respectively. 2021 Elsevier Masson SAS. All rights reserved.